Polymer Cancerostatics Targeted by Recombinant Antibody Fragments to GD2-Positive Tumor Cells - Pola, Robert; Král, Vlastimil; Filippov, Sergey K; Kaberov, Leonid; Etrych, Tomáš; Sieglová, Irena; Sedláček, Juraj; Fábry, Milan; Pechar, Michal (Biomacromolecules, 2019)
A water-soluble polymer cancerostatic actively targeted against cancer cells expressing a disialoganglioside antigen GD2 was designed, synthesized and characterized. A polymer conjugate of an antitumor drug doxorubicin with a N-(2-hydroxypropyl)methacrylamide-based copolymer was specifically targeted against GD2 antigen-positive tumor cells using a recombinant single chain fragment (scFv) of an anti-GD2 monoclonal antibody. The targeting protein ligand was attached to the polymer-drug conjugate either via a covalent bond between the amino groups of the protein using a traditional nonspecific aminolytic reaction with a reactive polymer precursor or via a noncovalent but highly specific interaction between bungarotoxin covalently linked to the polymer and the recombinant scFv modified with a C-terminal bungarotoxin-binding peptide. The GD2 antigen binding activity and GD2-specific cytotoxicity of the targeted noncovalent polymer-scFv complex proved to be superior to the covalent polymer-scFv conjugate.
Keywords: nádorové buněčné linie; Doxorubicin; Protein Binding; Bungarotoxins; Single-Chain Antibodies; Mice; Cell Proliferation; Cell Line, Tumor; buňky 3T3; Antineoplastic Agents; Gangliosides; 3T3 Cells; doxorubicin; kyseliny polymethakrylové; protinádorové látky; zvířata; nanokonjugáty; vazba proteinů; bungarotoxiny; Nanoconjugates; myši; proliferace buněk; gangliosidy; jednořetězcové protilátky; Polymethacrylic Acids; Animals